Analysis and evaluation of ADBMS rules activity - Laučius, Juozas; Ribikauskas , Arūnas; Trinkūnas , Justas (Lietuvos matematikos rinkinys, 2009)
Article presents analysis and evaluationof ECA rules activity.Most of active rules are implemented by triggers and functions. Sophisticated rules based systems have several problems including difficulty to control and analyse the system. We propose to use Functional Size Measurement Method to evaluate activity of rules in ADBMS. A function point is a unit of measurement to express the amount of businessfunctionality an information system provides to a user. Paper provides major reasons and benefits for using this method.